Hakikat Manusia Sebagai Makhluk Pedagogik, Fitrah, Alat-Alat Epistemik, Dan Hubungannya Dengan Teori Perkembangan Peserta Didik - Diansyah Permana; Aden Ginanjar; Moch Erdiansyah; Maad Adlani; Faizal HR; Nurlina (PT. Nawa Edukasi Nusantara, 2026)
This article examines the nature of humans as pedagogical beings, focusing on fitrah, epistemic tools, and their relationship with learner development theory. The main problem addressed in this study is the tendency of educational practice to emphasize cognitive achievement while paying less attention to the holistic nature of humans, including moral, spiritual, emotional, and epistemic dimensions. This study aims to analyze the concept of humans as pedagogical beings, explain the role of fitrah and epistemic tools in the educational process, and describe their relevance to learner development. This research uses a qualitative approach with a library research method. Data were obtained from books, journal articles, and relevant previous studies, then analyzed using content analysis through identification, classification, comparison, and synthesis of concepts. The results show that humans are essentially beings who can be educated and can educate others. Human fitrah serves as the basic potential that must be preserved and developed through education. Epistemic tools, including senses, reason, heart, and intuition, function as means for acquiring, processing, and internalizing knowledge. These findings indicate that learner development should be understood holistically, not only through cognitive and psychological aspects, but also through moral and spiritual dimensions. The study concludes that education should be humanistic, integrative, and oriented toward the development of the whole person.